Modelling the Evaporation Rate in an Impingement Jet Dryer with Multiple Nozzles - Anna-Lena Ljung; L. Robin Andersson; Anders G. Andersson; T. Staffan Lundström; Mats Eriksson (International Journal of Chemical Engineering)
Impinging jets are often used in industry to dry, cool, or heat items. In this work, a two-dimensional Computational Fluid Dynamics model is created to model an impingement jet dryer with a total of 9 pairs of nozzles that dries sheets of metal. Different methods to model the evaporation rate are studied, as well as the influence of recirculating the outlet air. For the studied conditions, the simulations show that the difference in evaporation rate between single- and two-component treatment of moist air is only around 5%, hence indicating that drying can be predicted with a simplified model where vapor is included as a nonreacting scalar. Furthermore, the humidity of the inlet air, as determined from the degree of recirculating outlet air, has a strong effect on the water evaporation rate. Results show that the metal sheet is dry at the exit if 85% of the air is recirculated, while approximately only 60% of the water has evaporated at a recirculation of 92,5%.